Pain modulatory network is influenced by sex and age in a healthy state and during osteoarthritis progression in rats. Issue 2 (5th January 2021) - Da Silva, Joyce T.; Tricou, Christina; Zhang, Youping; Tofighbakhsh, Amir; Seminowicz, David A.; Ro, Jin Y.
Abstract: Old age and female sex are risk factors for the development of osteoarthritis (OA) and chronic pain. We investigated the effects of sex and age on pain modulatory networks in a healthy state and during OA progression. We used functional MRI to determine the effects of sex and age on periaqueductal gray functional connectivity (PAG FC) in a healthy state (pre‐OA) and during the early and late phases of monosodium iodoacetate‐induced OA in rats. We then examined how sex and age affect longitudinal changes in PAG FC in OA. In a healthy state, females exhibited more widespread PAG FC than males, and this effect was exaggerated with aging. Young males had moderate PAG FC changes during the early phase but recruited additional brain regions, including the rostral anterior cingulate cortex (ACC), during the late phase. Young females exhibited widespread PAG FC in the early phase, which includes connections to insula, caudal ACC, and nucleus accumbens (NAc). Older groups had strong PAG FC with fewer regions in the early phase, but they recruited additional brain regions, including NAc, in the late phase. Overall, our findings show that PAG FC is modulated by sex and age in a healthy state. A widespread PAG network in the early phase of OA pain may contribute to the transition from acute to chronic OA pain and the increased risk of developing chronic pain for females. Enhanced PAG FC with the reward system may represent a potential mechanism underlying chronic OA pain in elderly patients. Abstract : In a healthy state, females exhibit widespread periaqueductal gray functional connectivity (PAG FC), and this effect is exaggerated with aging. Young females have widespread PAG network in the early phase of osteoarthritis (OA) pain. PAG FC with rostral anterior cingulate cortex in young males in the late OA phase may facilitate descending pain inhibition. Enhanced PAG FC with the reward system is seen in old groups in the late OA phase.